1991
DOI: 10.1007/bf02034932
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of bleomycin-induced lung damage

Abstract: Bleomycins are a family of compounds produced by Streptomyces verticillis. They have potent tumour killing properties which have given them an important place in cancer chemotherapy. They cause little marrow suppression, but pulmonary toxicity is a major adverse effect. The mechanisms of cell toxicity are well described based on in vitro experiments on DNA. The bleomycin molecule has two main structural components: a bithiazole component which partially intercalates into the DNA helix, parting the strands, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
212
1
4

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(226 citation statements)
references
References 152 publications
8
212
1
4
Order By: Relevance
“…In addition, in concert with the abundant evidence indicating that ROS is central to BLM-induced pulmonary fibrosis 25,[36][37][38] , our study demonstrate that alveolar type II epithelial cells in Elovl6 À / À mice produce more ROS than those in WT mice as assessed by staining with antibody against nitrotyrosine. These results help explain why Elovl6 À / À mice are more susceptible to BLM-induced pulmonary fibrosis.…”
Section: Blm Treatment Decreases Elovl6 Expression In the Lungsupporting
confidence: 77%
“…In addition, in concert with the abundant evidence indicating that ROS is central to BLM-induced pulmonary fibrosis 25,[36][37][38] , our study demonstrate that alveolar type II epithelial cells in Elovl6 À / À mice produce more ROS than those in WT mice as assessed by staining with antibody against nitrotyrosine. These results help explain why Elovl6 À / À mice are more susceptible to BLM-induced pulmonary fibrosis.…”
Section: Blm Treatment Decreases Elovl6 Expression In the Lungsupporting
confidence: 77%
“…However, BLM produces a dosedependent pulmonary fibrosis in most patients (8). A single intratracheal instillation of BLM is commonly used to induce experimental pulmonary fibrosis in rodents (11,12). In this animal model, the single application of the antibiotic causes an acute inflammatory reaction and fibrotic changes that resemble human fibrotic lung disease both histologically and physiologically (1,13,14).…”
mentioning
confidence: 99%
“…The availability of this animal model of pulmonary fibrosis provides the opportunity to investigate novel pharmacological approaches that can be used to treat and prevent this disease (12).…”
mentioning
confidence: 99%
“…Bleomycin administration is known to damage the lung epithelial cells resulting in lower cell numbers (Hay et al, 1991). The results from our colony forming assay in BALF demonstrated a reduction in colonyforming units on bleomycin treatment.…”
Section: Effects Of Plant Flavonoids In Idiopathic Pulmonary Fibrosismentioning
confidence: 48%
“…Although the exact mechanisms by which bleomycin causes pulmonary fibrosis remains unclear, it has been reported that, Reactive Oxygen Species (ROS) generated by bleomycin, causes direct injury to the lung epithelial cells (Banerjee et al, 2015;Hay et al, 1991;Wang et al, 2002). Reactive Oxygen Species such as superoxide anions, hydrogen peroxides, and hydroxyl radicals have been reported to play an important role as a mediator of bleo-induced lung fibrosis (Arslan et al, 2002;Chen and Stubbe, 2004).…”
Section: Effects Of Plant Flavonoids In Idiopathic Pulmonary Fibrosismentioning
confidence: 99%